Preparation of N-isopropyl acrylamide polymer gel dosimeters and their characterization by Raman spectroscopy - Adenan, Mohd Zulfadli (2014)
This present work aims to synthesise N-isopropyl acrylamide (NIPAM) polymer gel and study the effect of NIPAM monomer and N, N’-methylene-bisacrylamide (BIS) crosslinker concentrations on polymerization of NIPAM polymer and NIPAM and BIS consumptions in gelatin matrix induced by gamma rays at dose between 0 and 21 Gy. The NIPAM polymer gels were synthesized from NIPAM (2 to 4% w/w) and BIS (2 to 4% w/w), gelatin (6% w/w), anti-oxidant tetrakis hydroxymethyl phosphonium chloride (THPC) (5 mM), and de-ionized water. The samples were irradiated with 60Co Gamma cell instrument at a constant dose rate, receiving doses from 3 Gy up to 21 Gy. The dose response of irradiated NIPAM polymer gel was determined using Raman spectroscopy. Raman peak intensities were identified in the samples at 815 cm-1 assigned bonding for C-C of NIPAM polymer gel, 1025 cm-1 assigned bonding for C=C of NIPAM and 2353 cm-1 bonding for C=C of BIS. The Raman intensity y that corresponds to the rate of polymer formation in NIPAM polymer gel increases with increasing dose D and fitted with the monoexponential equation y = y0 + A(1 – e –D/D0 ). The dose sensitivity D0 derived from the equation that was also found increasing with the increase of initial concentrations of NIPAM monomer and BIS crosslinker. The rate of co-monomer consumption decreases with increasing dose and was fitted with the monoexponential equation y = y0 – A(1 – e -D/ D0). The dose sensitivity D0 were also found to increase with the increase of initial concentrations of NIPAM monomer and BIS crosslinker.